STRUKTUR GERAK TARI RADDAT ANAK DUYONG DI DESA BEKUT KECAMATAN TEBAS KABUPATEN SAMBAS KALIMANTAN BARAT - Cici Harniyanti; Ismunandar Ismunandar; Chiristianly Yery Silaban (Universitas Tanjungpura, 2020)
AbstractBackground research was to analyze the dance motions of Raddat Anak Duyong. The purpose of this research was to describe the motion structures dance of Raddat Anak Duyong through pictures. The method used was a descriptive method with a qualitative form through an ethnokoreological approach. Sources of data included Tamsi, Gumanto and Bandri who knew about the dance motions of Raddat Anak Duyong. Research Data was obtained through several techniques, including observations, interviews, and documentation. The main instrument in this study was researcher herself. The legality of data testing techniques used by researcher was the technique of observation extensions and triangulation techniques. Results of the study are: 1) analysis of the Raddat Anak Duyong motion structures with four kinds of motion, the initial motion, middle and ending motion analyzed based on themes, phrases, sentences, and clusters. 2) Lesson Plan (RPP) in accordance with the curriculum 2013 that applies to junior high school students. The results of the study can be a teaching material in grade 8th junior high school students of Art and Culture subject.Keywords : Dance Motion Structure, Raddat Anak Duyong Dance, Raddat Anak Duyong Dance Move